Technological methods of improving the quality and productivity of processing car engine parts - Kalchenko, Volodymyr; Venzheha, Volodymyr; Kuzhelnyi, Yaroslav; Klymenko, Valeriy; Кальченко, Володимир Віталійович; Венжега, Володимир Іванович; Кужельний, Ярослав Володимирович; Клименко, Валерій Іванович (Харківський національний автомобільно-дорожній університет, 2023)
Problem. The most high-precision parts of the car engine are camshaft and crankshaft, parts that require two-sided processing of the end surfaces: piston pins, valve springs. Traditional processing methods are used in their manufacture and repair. Therefore, taking into account the large volumes of car production, the improvement of existing and development of new processing methods is very important. Goal. The purpose of this work is the analysis and improvement of existing methods and the implementation for new ones of processing the specified parts to increase the productivity and accuracy of their processing. Methodology. The processing of support necks and cams is expedient to be carried out in one installation during deep high-speed grinding with crossed axes of the circle and camshaft due to stabilization of the cutting depth and feed along the contour with uneven rotation of the part. The method of high-speed milling of camshaft cams with crossed axes of the tool and parts on CNC machines is also promising. Root and connecting rod necks of crankshafts can be processed in one installation by deep high-speed grinding with crossed axes of the circle and the part due to stabilization of the depth of cutting and feed along the contour with uniform rotation of the part. For end surfaces, it is possible to introduce single-pass processing on double-sided end grinding machines with oriented grinding wheels with calibration areas. Results. The obtained results indicate a 25-30% increase in productivity and processing accuracy of the specified parts. Originality. It is used when processing the effect of the intersection of the axes of the tool and the part and carrying out a special correction of the tool, which allows to obtain a calibration area. Practical value. The proposed methods improve the parameters of accuracy, roughness and productivity of processing, which is an important scientific and practical task, whose solution will allow to increase the service life of car components and assemblies, reduce the cost of their production, and raise the level of competitiveness of products and services.
Технологічні методи підвищення якості та продуктивності обробки деталей двигунів автомобілів
Keywords: camshaft; crankshaft; piston pins; valve springs; high-speed milling; one-pass machining; розподільчий вал; колінчастий вал; поршневі пальці; клапанні пружини; високошвидкісне фрезерування; однопрохідна обробка; 629.3.08; 10.30977/AT.2219-8342.2023.52.0.03